HUBUNGAN PENGETAHUAN, SIKAP DENGAN PENERIMAAN PROGRAM VAKSINASI COVID 19 PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS RANGKASBITUNG KABUPATEN LEBAK - Gumelar, Yangyang Citra; Hastuti, Hera; Hakim, Fazuan Ratu; Sekarsari, Rita; Purwanto, Ika (NURSING ANALYSIS: Journal of Nursing Research, 2024)
ABSTRACTNumber of countries expressed skepticism about the safety, efficacy and side effects of Covid-19 vaccination that had slowen the acceleration of vaccination in almost all regions in Indonesia, and it was influenced by public knowledge about Covid-19 vaccination and public attitudes toward receiving the Covid-19 vaccine. The purpose of this study was to determine knowledge, attitudes toward acceptance in community in working area of Rangkasbitung Health Center, Lebak District.Methods: This type of research was correlational with cross sectional design. With Non- Probability Sampling technique, namely Accidental Sampling, 81 respondents with inclusion criteria in this study was people aged over 12 years old, who came to public health center where Covid-19 Vaccine was implemented .Results: from the analysis, most respondents had good knowledge (55.6%), had positive attitude, (45.7%), and vaccine acceptance (65.4%) female respondents (67.9%), respondents aged 18- 25 years old (55.6%), information related to covid-19 from social media (59.3%). The results of the bivariate analysis showed that there was relationship between knowledge (p=0.00 0) with acceptance of COVID-19 vaccination, it was found that there was no relationship (p= 0.922) between attitude with acceptance of Covid-19 vaccine in community in working area of Rangkasbitung Health Center.Conclusion: The conclusion in this study was that knowledge influenced the acceptance of COVID-19 vaccination and attitude did not affect the acceptance of COVID-19 vaccination in Work Area of Rangkasbitung Health Center.Keywords: Knowledge, Attitude, Acceptance of Covid-19 Vaccine                                                    ABSTRAKBanyaknya negara yang menyatakan skeptisme tentang keamanan, kemanjuran dan efeksamping membuat lambanya percepatan vaksinasi hampir di seluruh wilayah di indonesia hal ini dipengaruhi oleh pengetahuan masyarakat tentang vaksinasi Covid-19 dan sikap masyarakat terhadap peneriman vaksin Covid-19. Tujuan penelitian ini Untuk mengetahui pengetahuan, sikap dengan penerimaan pada masyarakat di wilayah kerja Puskesmas Rangkasbitung Kabupaten Lebak.Metode: Jenis penelitian ini adalah korelasional dengan desain cross sectional. dengan teknik pengambilan sampel Non- Probability Sampling yaitu dengan Accidental Sampling, sebanyak 81 responden dengan kriteria inklusi dalam penelitian ini adalah masyarakat dengan usia diatas 12 tahun, yang datang ke Puskesmas ke tempat pelaksanaan Vaksin Covid-19. Hasil: dari analisis sebagian besar responden mempunyai pengetahuan baik (55,6%), memiliki sikap positif, (45,7%), dan penerimaan vaksin (65,4%) responden perempuan (67,9%), responden usia 18-25 tahun (55,6%), informasi terkait covid-19 dari media sosial (59,3%). Hasil analisis bivariat diketahui terdapat hubungan antara pengetahuan (p=0,000) dengan penerimaan vaksinasi COVID-19, diketahui tidak ada hubungan (p=0,922) terhadap penerimaan vaksin Covid-19 pada masyarakat di wilayah kerja Puskesmas Rangkasbitung. Kesimpulan: Kesimpulan dalam penelitian ini pengetahuan berpengaruh dalam penerimaan vaksinasi COVID-19 dan sikap tidak berpengaruh dalam penerimaan vaksinasi COVID-19 di Wilayah Kerja Puskesmas Rangkasbitung. Kata Kunci : Pengetahuan, Sikap, Penerimaan Vaksin Covid-19